RECOMBINANT IGF-1 USE IN SIBLINGS WITH LARON SYNDROME: FIRST 2 CASES TREATED IN MALAYSIA - Samingan, Nurshadia; Mavinkurve, Meenal; Noordin, Mazidah; Leong, Annie; Zaini, Azriyanti Anuar; Yaakop, Siti Zarina; Jalaludin, Muhammad Yazid (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Laron Syndrome (LS) is a rare cause of extreme poor growth in children due to the mutation of GHR gene. It is characterised by postnatal growth failure, with midface hypoplasia and obesity. Growth hormone level is normal or elevated with low IGF 1 value. Severe short stature is the major disability in untreated adults. Recombinant IGF 1 hormone (rIGF1) is the only approved treatment since 2007. RESULTS We present the case of 2 siblings, whom parents are consanguineous. H presented at 11.5 years old with short stature and being obese; height 121 cm (-3.39 SDS), weight 41.8kg (+0.8 SDS) and BMI 28.55kg/m2 (+2.91 SDS). His birth weight and length were 3kg and 50 cm (-0.5 SDS and +0.3 SDS). Genetic test confirmed homozygous mutation at the GHR gene and presence of heterozygous gene mutation in both parents. The youngest sibling, K was born with birth weight of 3.2kg (+0.98 SDS). At 2.9 years old, K was severely stunted. His height and weight were 64.6cm (-7.67 SDS) and 6.18kg (-8.95 SDS). Both patients scored 4 out of 5 on Savage Scoring System. Recombinant IGF1 (mecasermin) was initiated at the age of 12.7 years and 4.1 years, respectively. At 10 months post rGH1, all growth parameters improved remarkably. Pre- and posttreatment height velocity and serum IGF 1 for H and K were (4.2cm vs 14.8cm)/year and (4cm vs 17.6cm)/year, (47 vs 329) Âµmol/L and (<15 vs 205) Âµmol/L, respectively. Hypoglycaemia, a common side effect of treatment was not reported. H’s percentage body fat and muscle mass improved from 54.1% to 52% and 10.8kg to 12.4kg. One year treatment for both siblings’ costs RM751,500 (USD 182,624.57) CONCLUSION LS is rare, yet a treatable cause for severe short stature. Albeit the exorbitant cost, treatment offers positive outlook.